VALUE APPROACH TO PROFESSIONAL ACTIVITY AS A FACTOR IN OVERCOMING THE NEGATIVE EFFECTS OF COGNITIVE DISSONANCE IN MEDICAL PATIENTS (Psychology Travelogs, 2025)
The article presents a theoretical analysis of the impact of cognitive dissonance on the professional activity of healthcare professionals. Using empirical data, the author outlines ways to neutralize and prevent the negative impact of cognitive dissonance in a professional context. The key conditions for the formation of a physician's conflict competence are adaptive strategies for overcoming stress, as well as value orientations that determine the attitude to life, work and interpersonal relationships.It is determined that the chosen strategies for dealing with difficulties affect the formation of “successful” and “unsuccessful” patterns of behavior of specialists. These patterns are manifested in the positive overcoming of the state of cognitive dissonance. This process has a positive impact on the structure, dynamics and effectiveness of personal processes, becoming a driver of self-improvement and potential disclosure. On the contrary, the negative consequence of overcoming cognitive dissonance is a discrepancy between the vision of “I-am-a-professional” and the ideal vision of “I am a professional”. This, in turn, leads to a feeling of dissatisfaction with one's own profession, the process of professional activity, and, as a result, to professional maladjustment.Studies have shown that coping strategies have a significant impact on how healthcare workers perceive cognitive dissonance. In particular, ineffective approaches to coping with stress can be a manifestation of cognitive dissonance, while adaptive strategies contribute to the growth of stress resistance among healthcare professionals.
Keywords: cognitive dissonance; culture of conflict resolution; health care workers; methods of overcoming difficulties; value-based attitude to professional activities